NEGOTIATION FOR MEANING AND CORRECTIVE FEEDBACK IN TEACHER- STUDENTS INTERACTION - Astuti, Cresensiana Widi (International Journal of Psychosocial Rehabilitation, 2020)
In interactional communication in English, language learners might find difficulties in expressing their thought and understanding their interlocutors’ utterances. Not only in social communication, but also in classroom interaction when language learners communicate with their teachers in English. This paper was aimed at finding, first, what learners do when they do not understand, second, how does the teacher respond to the learners’ errors, and third, the types of corrective feedback used by the teacher in responding to the learners’ errors. Data for this paper was collected by recording the interaction between a teacher and six students. They were interviewed on topics relevant to their future job as secretaries. The analysis was focused on the occurrence of negotiation for meaning, types of corrective feedback, and backchanneling behavior and disfluency markers. The results showed that the learners were willing to ask to clarify when they did not comprehend their interlocutor’s utterances. Their interlocutor reacted by giving the information needed or repeating the utterance, providing corrective feedback to the learners’ errors, and showing backchanneling. The data showed that recast was the most frequently used type of corrective feedback to which the learners responded in repair. The data showed some disfluency markers: false starts, fillers, self-correct utterances, and L1 influence. These findings might be useful in improving the interactional communication between teachers and students in which the teacher, as the more able person, is expected to give more room for the students to ask and to take some time before production.